The severity of field pea diseases depending on sowing rate and variety - Margit Olle; Pille Sooväli (Acta Agriculturae Scandinavica. Section B, Soil and Plant Science, 2020)
Six varieties of field pea (Pisum sativum L.) were sown at two sowing rates over two years to assess the impact on disease occurrence in a Baltic climate. The varieties used were Bruno (Latvia), Capella (Sweden), Clara (Sweden), Kirke (Estonia), Onward (Greece), and Vitra (Latvia). The two sowing rates were 120 seeds per m2 and 144 seeds per m2. The increase in sowing rate by 20% did not influence field pea diseases. Variety influenced the incidence of disease in field pea. The varieties most damaged by pod spot (Ascochyta blight caused by Ascochyta spp.) were Vitra and Onward and least damaged were Bruno and Clara. The variety most damaged by downy mildew (caused by Peronospora viciae) was Vitra and least damaged was Bruno. The variety most damaged by white mould (or Sclerotinia rot caused by Sclerotinia sclerotiorum (Lib.) de Bary) was Onward. The varieties that had the most disease damage were Vitra and Onward, while least susceptible were Clara and Bruno. Therefore, Clara and Bruno are recommended for field pea production in a Baltic climate.